Designing Procedurally Generated Levels - Linden, Roland; Lopes, Ricardo; Bidarra, Rafael (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2013)
There is an increasing demand to improve the procedural generation of game levels. Our approach empowers game designers to author and control level generators, by expressing gameplay-related design constraints. Graph grammars, resulting from these designer-expressed constraints, can generate sequences of desired player actions as well as their associated target content. These action graphs are used to determine layouts and content for game levels. We showcase this approach with a case study on a dungeon crawler game. Results allow us to conclude that our control mechanisms are both expressive and powerful, effectively supporting designers to procedurally generate levels.